Anti-phospholipid antibody syndrome with skin as a primary involved organ: an interesting case report - Soni, Aum N.; Parmar, Harshad V.; Prajapati, Hinal J. (International Journal of Research in Dermatology, 2024)
Anti-phospholipid antibody (APLA) syndrome is a multisystem vascular thrombopathy characterized by presence of antibodies against phospholipid antigens. Resulting thrombosis due to these antibodies leads to hallmark obstetric complications, cutaneous and cerebral vascular involvement, pulmonary embolism and thrombosis which can occur in vasculature of any organ system of body. Though APLA syndrome is characterized by pregnancy loss and foetal morbidity, isolated cutaneous or other system presentation has been reported especially in male patients. Here we present an interesting case report of an old aged male patient presenting with cutaneous ulcers and skin involvement as presenting feature.